The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5551/jat.54171
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Left Atrial Abnormality and B-Type Natriuretic Peptide in a General Japanese Population: NIPPON DATA2010

Abstract: Aims: P-wave terminal force in lead V1 (PTFV1) is an electrocardiogram marker of increased left atrial pressure and may be a noninvasive and early detectable marker for future cardiovascular events in the general population compared to serum B-type natriuretic peptide (BNP) concentration. The clinical significance of PTFV1 in the contemporary general population is an area of unmet need. We aimed to demonstrate the correlation between PTFV1 and BNP concentrations in a contemporary representative Japanese popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In a representative Finnish population sample the prevalences of abnormal PTFV1, partial, and advanced IAB were 4.9%, 11.8%, and 1.9% 32 . A Japanese study also demonstrated a prevalence for PTFV1 of 4.9% 33 . In another Finnish cohort, incidence rates for prolonged P‐wave duration, abnormal PTFV1, left P‐wave axis deviation, and right P‐wave axis deviation were found to be 16.0%, 7.4%, 3.4%, and 2.2%, respectively 34 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a representative Finnish population sample the prevalences of abnormal PTFV1, partial, and advanced IAB were 4.9%, 11.8%, and 1.9% 32 . A Japanese study also demonstrated a prevalence for PTFV1 of 4.9% 33 . In another Finnish cohort, incidence rates for prolonged P‐wave duration, abnormal PTFV1, left P‐wave axis deviation, and right P‐wave axis deviation were found to be 16.0%, 7.4%, 3.4%, and 2.2%, respectively 34 .…”
Section: Discussionmentioning
confidence: 88%
“… 32 A Japanese study also demonstrated a prevalence for PTFV1 of 4.9%. 33 In another Finnish cohort, incidence rates for prolonged P‐wave duration, abnormal PTFV1, left P‐wave axis deviation, and right P‐wave axis deviation were found to be 16.0%, 7.4%, 3.4%, and 2.2%, respectively. 34 In the large Atherosclerosis Risk in Communities (ARIC) study, the prevalence of abnormal P‐wave axis was comparable at 8.3%.…”
Section: Discussionmentioning
confidence: 95%
“…For example, a recent NIPPON DATA 2010 study showed that a subtle increase in serum B-type natriuretic peptide (BNP) was linked to electrocardiographic P-wave terminal force in lead V1 observed at baseline 7) . The linkage between electrocardiographic P-wave terminal force in lead V1 and long-term outcomes remains to be confirmed.…”
mentioning
confidence: 99%